Bioactive compounds of Curvularia species as a source of various biological activities and biotechnological applications - Mehta, Tushar; Meena, Mukesh; Nagda, Adhishree (Frontiers in Microbiology, 2022)
Many filamentous fungi are known to produce several secondary metabolites or bioactive compounds during their growth and reproduction with sort of various biological activities. Genus Curvularia (Pleosporaceae) is a dematiaceous filamentous fungus that exhibits a facultative pathogenic and endophytic lifestyle. It contains approximately 213 species among which Curvularia lunata, C. geniculata, C. clavata, C. pallescens, and C. andropogonis are well known. Among them, C. lunata is a major pathogenic species of various economical important crops especially cereals of tropical regions while other species like C. geniculata is of endophytic nature with numerous bioactive compounds. Curvularia species contain several diverse groups of secondary metabolites including alkaloids, terpenes, polyketides, and quinones. which possess various biological activities including anticancer, anti-inflammatory, antimicrobial, antioxidant and phytotoxicity. Several genes and gene factors are involved to carry and regulate the expression of these activities which are influenced by environmental signals. Some species of Curvularia also show negative impacts on humans and animals. Apart from their negativeeffects, there are some beneficial implications like production of enzymes of industrial value, bioherbicides and source of nanoparticles is reported. Many researchers are working on these aspects all over the world but there is no review in literature which provides significant understanding about these all aspects. Thus, this review will provide significant information about secondary metabolic diversity, their biological activities and biotechnological implications of Curvularia species.